An empirical analysis оn logistics performance and the global competitiveness - Yildiz, Turkay (Business: Theory and Practice, 2017)
Logistics has been identified as an area to build cost and service advantages. Therefore, companies are more focused on customer needs and trying to find ways to reduce costs, improve quality and meet the growing expectations of their clients. Indeed, the global competition has led managers to begin to address the issue of providing more efficient logistics services. In this regard, this paper presents an empirical study on logistics performance and global competitiveness. This paper also identifies the associations between logistics performances and global competitiveness. The results indicate that some variables in global competitiveness scores contribute much higher to the logistics performances than the other variables through analysis. The variables that contribute much higher than the other variables to the logistics performances are shown.